Periodic carbohydrate replacement during 50 min of high-intensity cycling improves subsequent sprint performance - Ball, T. C.; Headley, S. A.; Vanderburgh, P. M.; Smith, J. C. (International Journal of Sport Nutrition and Exercise Metabolism, 1995)
The purpose of this study was to investigate the effect of 7% carbohydrate-electrolyte (CE) drink on sprint capacity immediately following 50 min of high-intensity cycling. After an overnight 12-hr fast, 8 trained male cyclists performed two 50-min simulated time trials on a Monark stationary cycle ergometer. Subjects consumed either the CE or a flavored water placebo (PL) at 10, 20, 30, and 40 min during the time trial. At the conclusion of each 50-min time trial, subjects immediately performed a Wingate Anaerobic Power Test. Peak power, mean power, and minimum power were significantly higher for the CE trials, whereas mean RPE was significantly lower. Mean heart rate and fatigue index were not different between trials. These results suggest that sprint performance following a high-intensity simulated time trial of only 50 min can be improved with periodic consumption of CE during the ride, particularly following an overnight fast, when liver glycogen is likely to be low. These findings have implications for competitive cycling, where sprint capacity at the conclusion of a race is an important determinant of success.